A Minor Modification of Direct Browplasty Technique in a Patient with Brow Ptosis Secondary to Facial Paralysis: Copy-Paste-Excise and Stitch. (15th July 2013) - Taskiran Comez, Arzu; Gencer, Baran; Kara, Selcuk; Tufan, Hasan Ali
Abstract : Purpose . This report aimed to describe a minor modification of the traditional direct browplasty technique that aids in surgical planning for patients with brow ptosis secondary to facial paralysis without changing the shape of the brow. Case Report . A 74-year-old male patient with left facial paralysis secondary to chronic otitis media was referred with a complaint of low vision due to brow ptosis. We performed direct browplasty with a minor modification in order to aid a treatment customized to the patient. In this technique, a transparent film paper is used to copy the brow shape. A brow-shaped excision is facilitated just superior to the ptotic brow. Conclusion . The authors found that the copy-paste-excise and stitch technique was effective and successful for deciding the shape and the amount of excision that should be performed in patients with brow ptosis without resulting in asymmetrical, arched, and feminized brows.